THE RELEVANCE OF THEOLOGY OF PEOPLE IDEAS FOR THE PASTORAL WORK OF THE CATHOLIC CHURCH'S PREACHING - Jewadut, Jean Loustar; Muga, Richardus; Mansur, Inosentius (Bahasa Indonesia, 2025)
The task of preaching is one of the principal tasks of the Church. This article aims to provide a theological basis for the implementation of the pastoral work of contextual preaching and to offer synodality between the clergy and lay catechists in realizing the pastoral work of contextual preaching. All of this is studied comprehensively from the perspective of theology of people. Based on literature review, this article explains theology of people as a form of theology that rewards popular culture and religiosity that lives in society as a wealth that must be preserved. This study shows that the aspect of appreciation for popular culture and religiosity in society plays an important role in the pastoral proclamation of the Catholic Church. This is because transformative preaching is contextual preaching as a form of preaching that departs from the cultural wealth of the community. The realization of contextual preaching requires the active involvement of the clergy and lay catechists. They must familiarize themselves with the cultural context of the people, reflect on it with the people, and build a joint movement towards life transformation.